Psychometric properties of the Cyberbullying Scale for aggressors during virtual education (Revista Innova Educación, 2023)
The psychometric properties of the Cyberbullying Scale for aggressors in Peruvian adolescents were analyzed. This research has a non-experimental, quantitative, cross-sectional approach and instrumental design, in which 1019 adolescents of both sexes, students of public educational institutions of Secondary Level, aged between 12 to 17 years old (M=14; SD=1.56) participated. Results of the confirmatory factor analysis were χ2 = 103.725, p = 0.000, CFI = 0.965, TLI = 0.951 and RMSEA = 0.064. Likewise, convergent validity is reported, showing a moderate correlation between cyberbullying and cyberaggression (r= 0.548; p= 0.00) and an Omega Coefficient = 0.94. In conclusion, the scale consists of 8 items that measure cyberbullying caused by aggressors in an educational environment, whether face-to-face or virtual.
Keywords: Adolescents; cyberbullying; factor analysis; psychometric properties; virtual aggression